MENGUKUR KECEPATAN DAN PANJANG ANTRIAN MENGGUNAKAN APLIKASI GOOGLE MAPS - Setiawan, Setiawan; Munawar, Ahmad; Irawan, Muhammad Zuhdy (Teknisia, 2020)
Traffic survey is the main activity and is very important to get data on-road service performance for various traffic engineering purposes, transportation planning, road technical planning, and general planning (planning & programming). Google Maps could predict traffic conditions thanks to data collection collected from global positioning system (GPS) features. This study aims to analyze the comparison of travel speed data and queue length of Google Maps and field survey data. The survey conducted a vehicle speed survey using the MCO method while the length of the queue by counting the number of vehicles and the length of the queue at the intersection for comparison using the Google Maps application in the form of screenshot images or video. Theanalysis used by the Independent sample T-test is a type of statistical test that aims to compare the average of two groups that are not paired with or related to each other. Based on the T-test results, there is no difference in speed between survey results and Google Maps on Kusumanegara and AM Sangaji Utara roads. Based on the T-test results, there is no difference in queue length between the survey results and Google Maps on Kusumanegara and AM Sangaji Utara roads.